Transient behaviour of post-combustion CO2 capture with MEA in coal fired power plants - Gardarsdottir, Stefania Osk; Emilsdottir, Soley (My University, 2012)
CO2 emissions are recognized as a large contributing factor to global warming and climate change. Post-combustion CO2 capture has received significant attention as a possible near term option for reducing CO2 emissions from coal fired power plants as emissions from such plants are one of the major anthropogenic sources of CO2 in the world. Increased requirements for load flexibility in coal fired power plants make dynamic analysis of the capture process necessary. This thesis takes part in the development of a dynamic model of a CO2 absorption process with monoethanolamine (MEA) by constructing a reboiler model and by implementing strategies for process control. The model is applied to investigate the transient behaviour of the absorption system during and after load changes. The results show that the model gives a good understanding of the dynamic behaviour of the capture process. It is shown that the liquid-to-gas (L/G) ratio is more important than the actual flow rates for maintaining desired capture efficiency when the size of the system is not limiting the process. Results from load variations show that implementation of control strategies lowers the energy demand of the process considerably and this becomes clearer with larger load variations. It takes the system longer time to reach steady state with larger load variations, or 60 minutes at most. It takes the system around 20 seconds to respond to the load variations in all cases studied. The responses are generally smooth with little or no fluctuations and small overshoots. The fast system response and relatively small fluctuations and overshoots attained will facilitate integration with a power plant.
Keywords: Energi; Hållbar utveckling; Övrig annan teknik; Energy; Sustainable Development; Other Engineering and Technologies not elsewhere specified